LuxS and quorum-sensing in Campylobacter - Plummer, Paul (Frontiers in Cellular and Infection Microbiology, 2012)
Several intercellular bacterial communication mechanisms have been identified in a broad range of bacterial species. These systems, collectively termed quorum-sensing systems, have been demonstrated to play significant roles in a variety of bacterial processes including motility, biofilm formation, expression of virulence genes, and animal colonization. Campylobacter jejuni is known to possess a LuxS/ autoinducer-2 (AI-2) mediated system that have been partially characterized over the last decade. AI-2 is formed as a byproduct of the activated methyl recycling pathway, specifically by the LuxS enzyme. Previous work in our laboratory and that of others has demonstrated that this gene is involved in a variety of physiologic pathways of C. jejuni including motility, autoagglutination, cytolethal distending toxin (CDT) expression, flagellar expression, oxidative stress, and animal colonization. This review article will summarize the current research associated with LuxS in C. jejuni and will provide insights into the role of this system in the metabolism and intercellular communication of this organism. Additionally, the evidence for other quorum-sensing pathways in Campylobacter will be discussed.